Immunological markers of protective immune reconstitution in HIV infected persons sensitised by Mycobacterium tuberculosis - Jhilmeet, Nishtha (Department of Medicine, 2018)
Tuberculosis (TB) is the leading cause of death from a single infectious agent worldwide and HIV-1 co-infection is the leading cause of susceptibility to tuberculosis. Sub-Saharan Africa has a high incidence of TB-HIV-1 coinfection and the risk of TB in HIV-1 infected people is increased at all stages of the infection. Antiretroviral treatment (ART) is the most effective way to reduce the risk of TB in HIV-1 co-infected people. By studying the protective, ART induced immune reconstitution in HIV infected individuals sensitised by Mycobacterium tuberculosis (Mtb), we can identify correlates of protection against tuberculosis in the form of transcriptomic, soluble or cellular biomarkers. This thesis focuses on characterising Mtb-specific reconstituting CD4 T cells as well as soluble and transcriptomic markers in HIV infected persons, sensitised by Mtb, by analysing samples collected longitudinally during 6 months of ART. Analysis of peripheral blood mononuclear cells by 14-colour flow cytometry revealed the proportion and numbers of central memory CD4+ T cells significantly expanded in HIV infected persons on ART, while the proportion and numbers of effector memory and terminally differentiated effector CD4+ T cells decreased significantly. Additionally we noted a significant decrease in the proportion of activated CD4+ T cells, and IL-2 single producing CD4+ T cells in HIV infected persons at 6 months of ART, while polyfunctional Mtb specific CD4+ T cells secreting IFN-γ, IL-2 and TNF-α simultaneously, proportionally increased. Analysis of soluble markers in the plasma of HIV infected persons revealed an overall decrease in pro-inflammatory cytokines during 6 months of ART. A significant decrease in IFN-γ, IL-1α, IL-1β, IL-6, IL-17A and TNF-α was observed, and concentrations of these cytokines fell towards those observed in HIV uninfected persons. Transcriptomic analyses of 30 genes normalized to 3 different housekeeping genes, showed an overall increase in the expression of T cell memory specific genes, illustrating the regeneration of the memory T cell pool in HIV infected adults on ART. Larger number of central memory specific genes showed increased expression when normalised to at least two housekeeping genes, as compared to effector memory specific genes. These results support the reconstitution of central memory CD4 T-cell specific response at 6 months of ART. Our data provides insight into the reconstituting immune response to latent TB infection in the context of HIV infection and identifies potential correlates of decreased susceptibility to TB. We also show decreasing soluble and cellular factors indicative of decreasing immune activation in HIV infected persons receiving ART.